Growth analysis of wheat var. BARI gom-26 as affected by foliar spray of NAA at different nitrogen fertilizer levels - Islam, Saiful; Jahan, Nargis (Dhaka University Journal of Biological Sciences, 2016)
Leaf area index (LAI), crop growth rate (CGR), relative growth rate (RGR), net assimilation rate (NAR) and leaf area duration (LAD) of a variety of wheat (Triticum aestivum L.) were studied with three concentrations (0, 25 and 50 ppm) of naphthalene acetic acid (NAA) and four levels (0, 50, 75 and 100 %) of Nfertilizer in a field experiment during 2014 - 2015. Results showed that LAI and LAD at all stages of growth increased from control and their peak values were recorded mostly from 25 ppm NAA in combination with 75 % N-fertilizer and 50 ppm NAA in combination with 50% N-fertilizer. RGR was affected both positively and negatively depending on the concentration of NAA and nitrogen levels and was higher at earlier age (15 to 45 DAS) as opposed to later stage irrespective of treatments. CGR and NAR were also affected positively and negatively and tended to increase sharply reaching maximum at 30 - 45 DAS with a few exceptions and then decreased for most of the treatments with the progression of age. At 30 - 45 DAS, peak value of CGR was recorded from 25 ppm NAA in combination with 75% N-fertilizer. Of all the treatments, 25 ppm NAA in combination with 75% N-fertilizer produced better stimulation. Dhaka Univ. J. Biol. Sci. 25(2): 131-138, 2016 (July)